أصول التفسير وقواعده عند تفسير عبد الله بن عباس - Nirwana, Andri; Hidayat, Syamsul; Suharjianto, Suharjianto (Jurnal Studi Al-Qur'an, 2020)
The efforts of the Sahabah of the Prophet Muhammad saw, Abdullah ibn Abbas in developing the rules of interpretation, can be used by subsequent interpreters in developing interpretation rules in accordance with the times. Qaidah Tafseer only discusses the main points and lines of sharia law contained in the Qur'an, and then developed into a law detail. Qawaid Tafsir is not a means of justifying the truth in interpreting the Qur'an but only serves as a guardian of the methodology so that the resulting interpretation is objective, scientific, and accountable. Qiraat Science is a Muslim guide in reading the Qur'an. Abdullah bin Abbas has conveyed in his interpretation some Qiraat science that could be utilized by the next Ummah. Asbabun Nuzul is the study of the contextuality of a verse regarding events or questions. Abdullah bin Abbas was very close to the Prophet so that all knowledge of Asbabun Nuzul experienced at that time was very helpful in the interpretation of the Qur'an. Knowledge of Nasikh wal mansukh is very dependent from a historical point of view. The Companions of the Prophet knew very well where the verses that had been deleted the law and even the texts as well. The goodness of the Companions of the Prophet is because they live with the Prophet and have a strong memory. These four categories of knowledge are the concepts of Abdullah bin Abbas in interpreting the Qur'an.